2002
DOI: 10.1111/j.1432-2277.2002.tb00198.x
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of activated T cells and growth-factor production in the early and late phase of chronic kidney allograft nephropathy in rats

Abstract: T cells are thought to play a regulatory role in chronic allograft nephropathy (CAN). Thus, we investigated whether lymphocyte inhibition influences CAN. Fisher rat (F-344) kidneys were transplanted orthotopically into Lewis rats. Animals received cyclosporin A (1.5 mg/ kg per day, s.c.) for 10 days and were treated daily with either cyclosporin A (1.5 mg/kg), tacrolimus (0.16 mg/ kg), or a vehicle thereafter (n = 15 per group). Kidneys were harvested at 16 or 24 weeks. Interleukin-2 (IL-2) and interleukin-2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Therefore, the frequency of the TT genotype, which has been suggested to be high in IL‐2 low‐producers, was higher in patients with subclinical progressive CAN than in those without progressive CAN. Both cyclosporine and TAC inhibit IL‐2 and IL‐2 receptor beta 29 . Although serum IL‐2‐values were not measured in this study, we speculate that the influence of TAC on the inhibition of IL‐2 mRNA expression might be different according to the IL‐2 promoter genetic variation.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, the frequency of the TT genotype, which has been suggested to be high in IL‐2 low‐producers, was higher in patients with subclinical progressive CAN than in those without progressive CAN. Both cyclosporine and TAC inhibit IL‐2 and IL‐2 receptor beta 29 . Although serum IL‐2‐values were not measured in this study, we speculate that the influence of TAC on the inhibition of IL‐2 mRNA expression might be different according to the IL‐2 promoter genetic variation.…”
Section: Discussionmentioning
confidence: 75%
“…These agents can also partly act as fibrogenic signal molecules. 36,45 IFN-␥, the signature cytokine of Th1 cells, as well as the chemokines RANTES/CCL5, IP-10/CXCL10, MCP-1/CCL2, and MIP-1␣/CCL3 are implicated in the acute and chronic inflammatory rejection processes associated with CAN. 3,4,36 These cytokines were strongly down-regulated in the allografts treated with 13cRA.…”
Section: Discussionmentioning
confidence: 99%
“…33 In chronic renal allograft dysfunction a relationship between TGF-␤ mRNA expression and the intensity of cellular infiltration has been described. 45 TGF-␤1 promotes extracellular matrix accumulation by increasing matrix production and potentially by inhibition of matrix degradation (by induction of PAI-1). 46 Retinoids may have moderated fibrosis at least in part by reducing TGF-␤1 expression (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that T lymphocytes play a crucial role in the development of CAN. In experimental models, the progression of CAN has been delayed by a continuous suppression of T-cell activation and proliferation (26). FK778 suppresses T cell activation as well as lymphocyte proliferation (27).…”
Section: Discussionmentioning
confidence: 99%